Two new wasps (Insecta: Hymenoptera) from the Lower Cretaceous Sinuiju Formation of Ryonsang-dong, North Phyongan Province, Democratic People's Republic of Korea. (March 2022) - Won, Chol-Guk; So, Kwang-Sik
Abstract: Two new species of Hymenoptera are described from the Lower Cretaceous (Barremian–Aptian) Sinuiju Formation in Paektho-dong, Sinuiju City, North Phyongan Province, DPRK. They are: Karataus ryonsangensis sp. nov. (Ephialtitidae) and Pompilopterus ryonsangensis sp. nov. (Angarosphecidae). These fossils highlight the diversity of the hymenopterans from the Sinuiju Formation and the need to document the DPRK deposits. Highlights: Two new fossil wasps from the Sinuiju Formation were firstly discovered. They are Karataus ryonsangensis sp. nov . and Pompilopterus ryonsangensis sp . nov. They highlight the diversity of the hymenopterans from the Sinuiju Formation.